(untitled) (Journal of Parents and Teachers, 2024)
Learning a new language presents challenges that require an appropriate coping strategy. Effective communication and error identification are essential in the learning process. In addition, the importance of activities that encourage practice and comprehension is emphasized. The learner’s motivation and attitude are key factors in achieving success in this process.